The Readiness to Harness the Floristic Uniqueness of Mauritius in Biomedicine - Nawraj Rummun; Vidushi S. Neergheen (MDPI AG, 2023)
Resistance to the existing arsenal of therapeutic agents significantly impedes successful drug therapy. One approach to combat this burgeoning global crisis is to provide novel and more effective clinical agents. Terrestrial plants have long been exploited as a source of novel drug candidates. In this line, the endemic floral diversity of the Republic of Mauritius cannot be ignored. However, developing drugs from these plants is a multi-stepped, lengthy process that requires multistakeholder involvement from scientists, policymakers, and conservationists as well as the local community. This review aims at summarising the reported bioactivities of the endemic plants. The electronic databases were searched using relevant keywords. A total of 33 original research articles were considered. A repertoire of 17 families comprising 53 Mauritian-endemic plant species has been reported for their anticancer activity (n = 20), antimicrobial activity (n = 36), antidiabetic activity (n = 3), and clinical enzyme inhibitory activity (n = 25). Five plant extracts, namely Acalypha integrifolia, Labourdonaisia glauca, Eugenia tinifolia, Syzygium coriaceum, and Terminalia bentzoë, have been earmarked as worthy to be further investigated for their anticancer potential. Moreover, two Psiadia species, namely P. arguta and P. terebinthina, have shown promising antimicrobial activity. This review highlights the extracts' potent anticancer and antimicrobial activities, focussing on their proposed mechanism of action. Moreover, the need for metabolite profiling for identifying bioactive ingredient(s) is emphasised.